A Perylenediimide Tetramer‐Based 3D Electron Transport Material for Efficient Planar Perovskite Solar Cell. Issue 5 (8th May 2017) - Cheng, Ming; Li, Yuanyuan; Liu, Peng; Zhang, Fuguo; Hajian, Alireza; Wang, Haoxin; Li, Jiajia; Wang, Linqin; Kloo, Lars; Yang, Xichuan; Sun, Licheng
Abstract : A perylenediimide (PDI) tetramer‐based three dimensional (3D) molecular material, termed SFX‐PDI4, has been designed, synthesized, and characterized. The low‐lying HOMO and LUMO energy levels, high electron mobility and good film‐formation property make it a promising electron transport material (ETM) in inverted planar perovskite solar cells (PSCs). The device exhibits a high power conversion efficiency (PCE) of 15.3% with negligible hysteresis, which can rival that of device based on PC61 BM. These results demonstrate that three dimensional PDI‐based molecular materials could serve as high performance ETMs in PSCs. Abstract : For the first time, a fullerene free inverted planar structured perovskite solar cell (PSC) containing perylenediimide (PDI) tetramer‐based organic semiconductor as electron transport material is reported, achieving a high efficiency of 15.3% with negligible hysteresis.